THE OPTIMIZATION OF DISTRIBUTION SORTING TRACKS BETWEEN THE ASSIGNMENT PLAN FORMATION - Kozachenko, D. M.; Berezovyi, M. I.; Korobyova, R. H. (Science and Transport Progress, 2008)
The method of the sorting tracks assignment according to the destinations of the forming plan has been worked out. This method allows reducing the operational costs of the terminal sorting stations connected with the shunting operations for the forming up the unit and multi-unit trains.